Mapas, cartas e outras memórias: heterotopias possíveis no cartocontar - Pereira, Luís Henrique Ramalho (2022)
How to run on a political development in the training of psychologists? This is the main questioning that guides the work of the activities proposed by the School Suport Center (NAE). Since 2017, NAE has become an intervention project in the school-community of the Western region in the city of Santa Maria and aimed to deepen the interventions of the psychologists about the community and fundamentally to contribute to the training of the professionals. The approach of the psychologists in the school-community territory allowed the broadening of the view to more complex issues of the political life activities. Therefore, together with teachers, children and families, the psychologists in training understood the demands of the school-community and suggested ways to intervene in the community. In these findings in the school-community territory, the method used to investigate the formative-political effects is called cartocontar, a powerful instrument between the look of the psychologist in training and the operations carried out with the subjects involved. This thesis is related to the line of research of the research group on the social imaginary (GEPEIS). The study aims to investigate the formative experiences of the psychologists in the public space of the school, seeking to identify processes that indicate heterogeneous formative processes throught the cartocontar instrument resulting in an ethical and political formation. The main objective is to investigate how the forms of suffering that invade the school environment affect teachers, students and families in an important way. Is it possible that the learning-training process could happen without dispensing the potency of the ethical-political dimension? How can we seek a political education? This study aims to produce a reflection on the training processes of the psychologists from an experience of cartocontar by intervening in the school-community scene. The psychologists in training at the School Suport Center (NAE), developed by the Psychology Course from the Luthern University of Brazil (ULBRA), in Santa Maria through cartocontar instrument. The psychologists presented their experiences via their testimonial letters and the cartography of the texts produced along the formative experience. Starting from clinical-educational processes, with the proposal of producing presence-city writings, image maps and textual cartographies. In cartocontar the cartographer and the psychologists in training witness a political operator.